SISTEM PAKAR MENDETEKSI TINGKAT RESIKO PENYAKIT MELALUI GEJALA DAN POLA HIDUP MENGGUNAKAN METODE FUZZY MAMDANI - Allwine Allwine; Mutiara S. Simanjuntak; Rico Wijaya (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan)
Currently the expert system is growing rapidly moving along with the development of computer technology which is getting more and more advanced from day to day. Humans always try to make it easier to solve every problem faced. One application to solve every problem is an expert system for a healthy lifestyle.The importance of health for everyone in order to be able to empower everything that they have and their environment to the fullest, health is very closely related to healthy living. So that the definition of healthy living can be elaborated by having health in life with no problems with disruption in life both physical in the form of illness in the body and non-physical related to the condition of one's soul, heart and mind in life both individually and socially. The making of this expert system is carried out in the following stages: designing a healthy living program on eating rules, so as to create an expert system design with a tracking model with the Fuzzy Logic method. The making of this expert system uses the Microsoft Visual Basic 2008 programming language.